2006
DOI: 10.1074/jbc.m602373200
|View full text |Cite
|
Sign up to set email alerts
|

Active Transcription of the Human FASL/CD95L/TNFSF6 Promoter Region in T Lymphocytes Involves Chromatin Remodeling

Abstract: Fas ligand (FasL/CD95L/TNFSF6), a member of the tumor necrosis factor family, initiates apoptosis in lymphoid and nonlymphoid tissues by binding to its receptor Fas (CD95/TNFRSF6). Although the transcriptional control of TNFSF6 gene expression is subjected to intense study, the role of its chromatin organization and accessibility to the transcriptional machinery is not known. Here, we determined the chromatin organization of TNFSF6 gene 5 regulatory regions. Using the indirect end-labeling technique, a unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…Importantly, these data show that coordinated H3K4/H3K9 methylation/demethylation plays a significant role in the regulation of activation-induced FasL gene expression under normal as well as pathologic conditions. Similar co-ordinated modulation of H3K4 and H3K9 methylation has also been observed as a regulatory feature of other actively transcribed genes (22, 23, 28, 5052). …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Importantly, these data show that coordinated H3K4/H3K9 methylation/demethylation plays a significant role in the regulation of activation-induced FasL gene expression under normal as well as pathologic conditions. Similar co-ordinated modulation of H3K4 and H3K9 methylation has also been observed as a regulatory feature of other actively transcribed genes (22, 23, 28, 5052). …”
Section: Discussionsupporting
confidence: 67%
“…Earlier work, based on DNAse hypersensitivity of the FasL 5′-regulatory region indicated that chromatin remodeling is a primary event in the transcriptional activation of FasL gene expression (28). To further elucidate the epigenetic mechanisms underlying FasL promoter chromatin remodeling and transcriptional activation, we examined the TCR-stimulation responsive histone modifications in primary human CD4+ T lymphocytes under normal and the pathologic conditions of alcohol exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclei were purified and submitted to nuclease digestion as previously described [21]. Briefly, cells were lysed at 4°C in 0.2% NP40 buffer followed by nuclease digestion using DNase I (10 min at 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…However, the role of FasL expression and apoptotic death in AZT induced hepatotoxicity has not been examined. We and others have shown that promoter-associated epigenetic modifications are known to regulate FasL gene expression (Castellano et al, 2006; Ghare et al, 2014; Holtz-Heppelmann et al, 1998; Li-Weber and Krammer, 2003). Hence, the present study examines the potential hepatotoxic interactions between acrolein and the ART drug, AZT.…”
Section: Introductionmentioning
confidence: 99%